2020
DOI: 10.4102/phcfm.v12i1.2263
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to prescription-writing guidelines for outpatients in Southern Gauteng district hospitals

Abstract: Background Medical prescription writing is legally and professionally regulated in order to prevent errors that can result in patients being harmed. This study assesses prescriber adherence to such regulations in primary care settings. Methods A cross-sectional study of 412 prescriptions from four district hospital outpatient departments (OPDs) was conducted in March 2015. Primary outcome data were obtained by scoring prescriptions for accuracy across four categories: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Higher adherence to guidelines will actually lead to treatment regimen completion possibly because of the institutional culture of emphasizing on the treatment regimen prescription writing. (51) In conclusion, the pattern of prescriptions revealed inappropriate practices in the form of multiple drugs, use of brand names, prescribing xed dose combinations and overuse of antibiotics without any rationale and not adhering to the available guidelines (ICMR, State, WHO). Though the guidelines have overlaps, they are not all the same and also do not include all the possible treatment options creating a scope for physician to depend on his/her experience/expertise.…”
Section: Discussionmentioning
confidence: 89%
“…Higher adherence to guidelines will actually lead to treatment regimen completion possibly because of the institutional culture of emphasizing on the treatment regimen prescription writing. (51) In conclusion, the pattern of prescriptions revealed inappropriate practices in the form of multiple drugs, use of brand names, prescribing xed dose combinations and overuse of antibiotics without any rationale and not adhering to the available guidelines (ICMR, State, WHO). Though the guidelines have overlaps, they are not all the same and also do not include all the possible treatment options creating a scope for physician to depend on his/her experience/expertise.…”
Section: Discussionmentioning
confidence: 89%
“…[ 59 ] In Pakistan, the name of drug, dose, dosage form, and how to use was mentioned in 100, 88, 97, 97% of prescriptions, respectively [ 52 ]. However, the lower rate of adherence to complete treatment-related information on prescriptions was also reported in South Africa [ 60 ]. Medication errors, drug-related adverse events, and therapeutic failure could occur when medications are dispensed with insufficient labels [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study completed at outpatient clinics in Saudi Arabia reported omissions of various components of the treatment regimen, with some reaching up to 91% incompleteness [ 39 ]. Higher adherence to guidelines will actually lead to treatment regimen completion, possibly because of the institutional culture of emphasising the treatment regimen prescription writing [ 40 ].…”
Section: Discussionmentioning
confidence: 99%